DISCOURSE OF RADICALISM THROUGH SOCIAL MEDIA IN INDONESIA - Wahyudi Tianotak; Muhsin Labib; Hasyim Adnani; Hafidz Alkaff (Sadra International Institute, 2024)
The problem of radicalism in Indonesia has become a serious threatplayed by certain parties. The spread of radical ideology is not onlycarried out in the real world, but has shifted to social media since the world entered a fairly rapid technological era. Through social media,radical groups not only spread radical understanding, but also invite their users to join them. Therefore, this study explores the dynamics of discourse of radicalism through social media in Indonesia, focusing on novel aspects of interaction patterns, narrative content, an impact on social media users. Urgency of this research is to discuss how radical groups can exist through social media in Indonesia. Meanwhile, the methodology used in this research is descriptiveanalytical which based on Herrold Lasswel Communication Theory namely who, say what, in which channel, to whom, with what effect. In addition, the results of this research show that the existence of radical groups on social media is influenced by four factors, namely domestic factors, international political factors, cultural factors, and radical group transformation factors. In Indonesia, how radical groups can exist through social media, has at least four indirect distribution patterns, namely using social media accounts, conducting private chat communications, holding face-to-face meetings, and holding a coaching process for sympathizers and their groups.